Relationship Between Workload And Caring Behavior And Patient Safety Implementation In The Emergency Installation Room (Nursing Care Journal, 2023)
Installation Emergency Emergency (IGD) is a unit in a hospital that is designed and used For give standard maintenance emergency emergency with fast , precise , and alert every when , and accuracy For prevent happen disability or death in patients . Therefore, nurses try to provide the best service . This can be a burden on individuals . Workload increase fatigue work . Fatigue in general emotional This influential to service nursing careprovided one of them that is behavior caring nurses . The decrease in caring also has an effect to giving implementation patient safety during the ER. Purpose of the study this is to analyze connection burden Work withcaring nurses and implementation patient safety in the SMC Emergency Room of Telogorejo Hospital Semarang. The sampling technique used was total sampling . The data collection tools used were the Gadar Caring Scale(GCS-46 ) and the patient safety implementation observation sheet . Data analysis used the Pearson product moment test. and Spearman rank. The results of the statistical test showed that there was a relationship betweenworkload and nurse caring behavior ( P value 0.002) and there was no relationship between workload and patient safety implementation (P value 0.034). Where, the more tall burden Work nurse can influence behavior caring and implementation of implementation patient safety nurse at the SMC Emergency Room, Telogorejo Hospital. Nurses can show a loss of empathy and sympathy for patients, in addition it can also cause a decrease in nurse performance in carrying out appropriate nursing actions. It is hoped that further researchers can pay attention to other factors regarding nurses' workload